Getting to Net-Zero Emissions: Lessons from Latin America and the Caribbean (Inter-American Development Bank, 2019)
All Latin America and the Caribbean countries have ratified the Paris Agreement, which aims to limit global warming to between 1.5C and 2C above pre-industrial levels. Those goals require reaching net-zero carbon dioxide emissions by around 2050 and substantial reductions of CO2 emissions by 2030. Getting to Net-Zero Emissions takes stock of the lessons learnt from the experiences of country teams implementing the ongoing IDB-led Deep Decarbonization Pathways in Latin America and the Caribbean Project and proposes approaches to developing and delivering long-term pathways to net-zero emissions by 2050. The report shows the essential role played by long-term strategies in terms of identifying and planning the deployment of the infrastructure and policy packages necessary to ensure a just transition towards a net-zero emission economy. Long-term strategies will help governments anticipate fiscal and financial costs, manage trade-offs, minimize social impacts, and define the sequence of policy reforms and investment priorities required to deliver a carbon-neutral future. The design of long-term strategies by 2020 in line with the timeline envisaged in the context of the Paris Agreement can guide the establishment of more ambitious Nationally Determined Contributions (NDCs) and minimize stranded assets and associated costs. Long-term strategies are an essential instrument, both to contribute to the redirection of public and private investments, and to guide the dialogue with development institutions seeking to support sustainable and inclusive development. By reading this report, we hope that decision makers and technicians will gain insights into how to deliver decarbonization successfully. – – Todos los países de América Latina y el Caribe han ratificado el Acuerdo de París, cuyo objetivo es limitar el calentamiento global a entre 1.5C y 2C por encima de los niveles preindustriales. Esos objetivos requieren alcanzar cero emisiones netas de dióxido de carbono para el a\~no 2050 y reducciones sustanciales de las emisiones de otros gases de efecto de invernadero. Este informe compila lecciones aprendidas de las experiencias de los equipos en los países que implementan el proyecto Rutas de Descarbonización Profunda en América Latina y el Caribe (DDPLAC) liderado por el BID. El informe muestra el papel esencial que desempe\~nan las estrategias a largo plazo en términos de identificación de infraestructura y políticas públicas necesarias para garantizar una transición justa hacia una economía de cero emisiones netas. Las estrategias a largo plazo ayudarán a los gobiernos a identificar las transformaciones requeridas para descarbonizar y los beneficios económicos asociados tanto al uso de tecnologías modernas y más eficientes y a las sinergias entre descarbonización y desarrollo económico. Las estrategias a largo plazo también permiten anticipar y gestionar los costos fiscales y financieros, minimizar y compensar posibles impactos sociales, y definir una secuencia de reformas de políticas e inversiones públicas necesarias para lograr un futuro neutral en carbono. El dise\~no de estrategias a largo plazo en el 2020, en línea con el cronograma previsto en el contexto del Acuerdo de París, puede apoyar el establecimiento de Contribuciones Determinadas Nacionalmente (NDC) más ambiciosas que minimicen los activos abandonados y los costos asociados. Finalmente, las estrategias a largo plazo son un instrumento esencial para guiar el diálogo con los organismos internacionales de cooperación y desarrollo que buscan apoyar el desarrollo sostenible e inclusivo. Al leer este informe, esperamos que los tomadores de decisiones y los técnicos obtengan información sobre cómo cumplir con el imperativo de la descarbonización de manera que mejore las vidas de los latinoamericanos y caribe\~nos.
Keywords: 330; climate change